2019
DOI: 10.3390/w12010110
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Wastewater Phosphorus Removal in Winter Temperatures Using an Anaerobic–Critical Aerobic Strategy in a Pilot-Scale Sequencing Batch Reactor

Abstract: Biological phosphorus removal using an anaerobic-aerobic sequencing batch reactor (SBR) in a low temperature can be difficult to remove, and aeration always accounts for nearly half of the total electricity costs at many wastewater treatment plants. In this study, a pilot-scale anaerobic-critical aerobic SBR (A-CA SBR) was developed for synthetic domestic wastewater. More importantly, the phase, whose concentration of diffused oxygen was controlled at 1.0-1.5 mg/L, was defined as a critical aerobic phase, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Capacity to biologically remove this nutrient will significantly reduce operational costs as biological phosphorus removal is one of the most cost-effective methods of phosphorus removal [14]. To date there has been limited success on a consistent basis for biological P removal within the dairy industry, with many systems often suffering from inconsistent or inadequate performance, and it is reported that although there has been extensive research into biological P removal in SBRs at lab scale, research into biological P removal at pilot scale is not as well documented, thus highlighting the need to conduct research at pilot scales to demonstrate how stable P removal can be achieved on-site [14,38]. Novel methods of biological phosphorus removal which are more robust will allow operators to reduce chemical use and cost.…”
Section: Overview Of Contaminant Removal Throughout the Studymentioning
confidence: 99%
“…Capacity to biologically remove this nutrient will significantly reduce operational costs as biological phosphorus removal is one of the most cost-effective methods of phosphorus removal [14]. To date there has been limited success on a consistent basis for biological P removal within the dairy industry, with many systems often suffering from inconsistent or inadequate performance, and it is reported that although there has been extensive research into biological P removal in SBRs at lab scale, research into biological P removal at pilot scale is not as well documented, thus highlighting the need to conduct research at pilot scales to demonstrate how stable P removal can be achieved on-site [14,38]. Novel methods of biological phosphorus removal which are more robust will allow operators to reduce chemical use and cost.…”
Section: Overview Of Contaminant Removal Throughout the Studymentioning
confidence: 99%